2016
DOI: 10.1177/1062860616656250
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Patient Navigation Program Improves Compliance With Adjuvant Breast Cancer Therapy in a Public Hospital

Abstract: Cancer health disparities affecting low-income and minority patients have been well documented to lead to poor outcomes. This report examines the impact of patient navigation on adherence to prescribed adjuvant breast cancer treatment. A multidisciplinary patient navigation program was initiated at a public safety net hospital to improve compliance with 3 National Quality Forum measures: (1) administration of combination chemotherapy for women with Stage (defined by the American Joint Committee on Cancer [AJCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Seventeen articles focused on the efficacy of PN for the receipt of cancer treatment . The majority of these studies focused on breast cancer (n = 14 [82%]), which was followed by colorectal cancer (n = 3 [18%]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen articles focused on the efficacy of PN for the receipt of cancer treatment . The majority of these studies focused on breast cancer (n = 14 [82%]), which was followed by colorectal cancer (n = 3 [18%]).…”
Section: Resultsmentioning
confidence: 99%
“…104,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] The majority of these studies focused on breast cancer (n = 14 [82%]), which was followed by colorectal cancer (n = 3 [18%]). Thirteen articles reported that PN had a positive impact on cancer treatment, including a shorter time to treatment initiation (n = 9 [53%]), 104,109,110,[112][113][114]117,119,121 higher rates of treatment reception or adherence (n = 6 [35%]), 107,108,112,115,116,118 and increased patient satisfaction with cancer care (n = 1 [6%]). 117 Four Cancer August 15, 2019 studies focused on community-based health care facilities, 109,111,119,120 and 3 studies addressed Latinas and American Indians.…”
Section: Treatmentmentioning
confidence: 99%
“…Ramirez and colleagues [17] in six city study and Lobb [18] in a multisite program in one state both found a benefit in time to initiation of treatment. Studies by both Castaldi and colleagues [19], and Raj and colleagues found a benefit in completion of guideline recommended treatment. The Patient Navigation Research Program, the largest study to date of patient navigation located at nine sites across the US showed benefits in cancer care, with a greater proportion of patients initiating cancer care in a timely fashion [20], with the benefits focused on those who had not initiated cancer care within 90 days of diagnosis.…”
Section: Patient Navigation In Cancer Carementioning
confidence: 94%
“…This approach has been proven to enhance the patient experience, reduce costs, and improve clinical outcomes. [4][5][6] Similar to the role of patient navigators, tumor board or multidisciplinary care discussions also provide a structured opportunity to improve care. Studies have noted that between 27% to 40% of treatment plans could change as a result of a tumor board discussion.…”
mentioning
confidence: 99%